AGROFORESTRY TECHNIQUES ON PEATLAND IN SABARU VILLAGE, PALANGKARAYA - Yanarita, Yanarita; Rotinsulu, Johanna M (The Journal is published by Graduate Programe of Lambung Mangkurat University, 2016)
Central Kalimantan with an area of 15,356,400 hectares have the degraded area of 4,636,890 hectares, some of which are peatlands. Peatlands are different from mineral lands or other organic lands. The chemical properties and characteristics of the peat including high acidity, low nutrient availability, and level of pyrite or sulfur should become the critical concerns for the success of land rehabilitation. One of the rehabilitation measures for degraded peatlands is by carrying out agroforestry techniques, the cropping patterns combining forest and agricultural crops that are mutually synergistic, with the goal of timber production in the long-term and crop production in the short term to meet the daily needs. The community development on agroforestry techniques on peatland in Sabaru Village, Palangkaraya, is one way to provide the insight to public to use lands to increase their income while improving and increasing the land productivity. The methods used in the agroforestry techniques in the village were the extension and training. The selected forest crop was meranti (Shorea Belangeran) and the perennial crops were petai (Parkia speciosa), mango (Mangifera indica) and rambutan (Niphelium lappaceum), while the agricultural crops were okra (Abelmoschus esculentus) and cayenne pepper (Capsicum frutescens), and the versatile crops turmeric (Curcuma domestica), lemongrass (Cymbopogon nardus), red ginger (Zingiber officinale Var. Rubrum Rhizoma), and kencur (Kaempferia galanga L.). The extension was performed by introducing the types of forest and agricultural crops, land preparation, planting techniques, and maintenance. The training was conducted by carrying out direct practices of agroforestry techniques, which created a pilot project on an area of 0.5 hectares. After 5 months, the results showed that Shorea Belangeran and Parkia speciosa had the growth percentage of 90%. Although the agricultural and versatile crops grew well, they were used only for everyday purposes.